2010
DOI: 10.1051/agro/2010002
|View full text |Cite
|
Sign up to set email alerts
|

Improving nitrogen fertilization in rice by sitespecific N management. A review

Abstract: Excessive nitrogen (N) application to rice (Oryza sativa L.) crop in China causes environmental pollution, increases the cost of rice farming, reduces grain yield and contributes to global warming. Scientists from the International Rice Research Institute have collaborated with partners in China to improve rice N fertilization through site-specific N management (SSNM) in China since 1997. Field experiments and demonstration trials were conducted initially in Zhejiang province and gradually expanded to Guangdon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
177
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 459 publications
(212 citation statements)
references
References 19 publications
8
177
0
Order By: Relevance
“…Reduction in N application usually promotes NUE especially for PFPN (Peng et al, 2010). The results of present study also exhibited that PFPN significantly increased as N rate reduced (Fig.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Reduction in N application usually promotes NUE especially for PFPN (Peng et al, 2010). The results of present study also exhibited that PFPN significantly increased as N rate reduced (Fig.…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, Bhatia et al (2012) suggested a 12.5% reduction in N application during early vegetative stage could increase rice yield. These studies clearly demonstrated a moderate reduction in basal N application rate rice cropping innovation for higher NUE (Peng et al, 2010). Therefore, dense planting with less N application at early growing stage (e.g.…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…Increase in fertilizer nutrient input, especially nitrogen fertilizer, has contributed significantly to the improvement of crop yields (Cassman et al, 2003). China's national average nitrogen rate for rice was 193 kg ha −1 in 2006 (Peng et al, 2010). Nitrogen rates are ranged from 150 to 250 kg ha −1 , depending on rice planting areas (Wang et al, 2001;Peng et al, 2006).…”
Section: Discussionmentioning
confidence: 99%